IMPROVING STUDENTS’ VOCABULARY USING POSTER MEDIA FOR SECOND GRADE HEARING DISABLE AT SMALB - Iis Siti Sa'adah; Ani Atikah (IKIP Siliwangi, 2019)
The objective of the study is to improve vocabulary in children with special need. The researchers have chosen the object in the school because, the school has lack of learning media and teachers. This research used the